Evaluation of Light-Emitting Diode Luminaire For Two-Lanes Roadway Lighting System - Padungsak Wannapasert; Santipont Ananwattanaporn; Atthapol Ngaopitakkul (My University, 2024)
Lighting systems for roadways are an important aspect of the transportation system in terms of safety and providing comfort for drivers. Conventional lighting systems use high-pressure sodium luminaires, which consume a lot of energy. This paper proposes an evaluation of roadway lighting using lightemitting diodes (LEDs) as luminaires. The paper uses a two-lane road as a case study and simulates the lighting parameters using DIALux software. The case study varies the wattage of the luminaires, pole distances, and pole arrangements, while keeping the pole specifications fixed. The parameters under consideration include illuminance, luminance, and uniformity on the road surface. Additionally, the results are compared with international criteria standards to confirm that the selected LED luminaires can provide the necessary lighting quality for road usage. The results show that LED luminaires can provide lighting quality within standard criteria. However, different pole arrangements require different levels of wattage and pole distances. Therefore, the selection of LEDs needs to match the design of pole distances and arrangements to provide sufficient roadway lighting.
Keywords: Impact of Light on Environment and Health; Vehicle emissions and performance; Safety Warnings and Signage